2011
DOI: 10.1126/science.1202617
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Proteins Targeting the Conserved Stem Region of Influenza Hemagglutinin

Abstract: We describe a general computational method for designing proteins that bind a surface patch of interest on a target macromolecule. Favorable interactions between disembodied amino-acid residues and the target surface are identified and used to anchor de novo designed interfaces. The method was used to design proteins that bind a conserved surface patch on the stem of the influenza hemagglutinin (HA) from the 1918 H1N1 pandemic virus. After affinity maturation, two of the designed proteins, HB36 and HB80, bind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
596
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 549 publications
(610 citation statements)
references
References 20 publications
8
596
1
5
Order By: Relevance
“…de novo design | protein design | ideal protein | control protein shape P rotein design holds promise for applications ranging from therapeutics to biomaterials, with recent progress in designing small molecule binding proteins (1,2), inhibitors of protein-protein interactions (3,4), and self-assembling nanomaterials (5)(6)(7). Most of these efforts have repurposed naturally occurring scaffolds, which are likely not optimal starting points for creating new functions because they generally contain sequence and structural idiosyncrasies that arose during evolutionary optimization for their natural functions (8).…”
mentioning
confidence: 99%
“…de novo design | protein design | ideal protein | control protein shape P rotein design holds promise for applications ranging from therapeutics to biomaterials, with recent progress in designing small molecule binding proteins (1,2), inhibitors of protein-protein interactions (3,4), and self-assembling nanomaterials (5)(6)(7). Most of these efforts have repurposed naturally occurring scaffolds, which are likely not optimal starting points for creating new functions because they generally contain sequence and structural idiosyncrasies that arose during evolutionary optimization for their natural functions (8).…”
mentioning
confidence: 99%
“…The crowd-sourced protein folding and design 'games' undertaken by the global Foldit community to identify inhibitors that bind and inhibit the 1918 pandemic influenza virus have shown that distributed problem solving in medicine and health can be very powerful (Fleishman et al 2011).…”
Section: Research Agendas For Global Healthmentioning
confidence: 99%
“…We have tested two assay stack formats utilizing two different binders. The first is an HA stem-region binder, which was originally reported by Fleishman et al [14] and has since been optimized by Whitehead et al [15]. The second protein is an HA head-region binder, which is under development with a publication in progress.…”
mentioning
confidence: 99%